Electrochemistry as a surrogate for protein phosphorylation: voltage-controlled assembly of reflectin A1. Issue 173 (23rd December 2020) - Liang, Sheng-Ping; Levenson, Robert; Malady, Brandon; Gordon, Michael J.; Morse, Daniel E.; Sepunaru, Lior
Abstract : Phosphorylation is among the most widely distributed mechanisms regulating the tunable structure and function of proteins in response to neuronal, hormonal and environmental signals. We demonstrate here that the low-voltage electrochemical reduction of histidine residues in reflectin A1, a protein that mediates the neuronal fine-tuning of colour reflected from skin cells for camouflage and communication in squids, acts as an in vitro surrogate for phosphorylation in vivo, driving the assembly previously shown to regulate its function. Using micro-drop voltammetry and a newly designed electrochemical cell integrated with an instrument measuring dynamic light scattering, we demonstrate selective reduction of the imidazolium side chains of histidine in monomers, oligopeptides and this complex protein in solution. The formal reduction potential of imidazolium proves readily distinguishable from those of hydronium and primary amines, allowing unequivocal confirmation of the direct and energetically selective deprotonation of histidine in the protein. The resulting 'electro-assembly' provides a new approach to probe, understand, and control the mechanisms that dynamically tune protein structure and function in normal physiology and disease. With its abilities to serve as a surrogate for phosphorylation and other mechanisms of charge neutralization, and to potentially isolate early intermediates in protein assembly, this method may be useful for analysing never-before-seen early intermediates in the phosphorylation-driven assembly of other proteins in normal physiology and disease.